A preparation method of surface modified lithium ion battery hard carbon negative electrode material
By surface modification on the hard carbon anode material of lithium-ion batteries, furfural resin microspheres are prepared using polycondensation raw materials such as phenol, alkyl alcohol phenol compounds and furfural, and modified with thienyl silane coupling agent and polythiophene coating, the problem of insufficient cycle stability and rate performance of existing hard carbon anode materials is solved, and higher cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411987826.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing hard carbon anode materials for lithium-ion batteries have shortcomings in terms of cycle stability and rate performance, resulting in poor cycle stability and poor rate performance of the battery.
Furfural resin microspheres were prepared by using phenol, alkyl alcohol phenol compounds and furfural as polycondensation raw materials, and modified by thienyl silane coupling agent. The modified furfural resin microspheres were then coated with polythiophene by surface in situ synthesis and carbonized to obtain a surface-modified lithium-ion battery hard carbon negative electrode material.
This method improves the adsorption capacity of lithium ions and the first Coulomb efficiency by forming active sites of sulfur elements, and improves the interfacial binding force and sulfur doping uniformity through the coating of polythiophene, significantly improving the cycling stability and rate performance of the battery.
Smart Images

Figure BDA0005222984590000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hard carbon negative electrode materials, and in particular relates to a method for preparing a surface-modified lithium ion hard carbon negative electrode material. Background Art
[0002] Lithium-ion batteries have become an ideal power source for small and lightweight electronic devices such as cameras, mobile phones, laptops and portable measuring instruments due to their outstanding advantages such as high operating voltage, light weight, high specific energy, low self-discharge, long cycle life, no memory effect and no pollution. They are also the preferred power source for high-energy power batteries in future automobiles.
[0003] The negative electrode material is an important component of lithium-ion batteries. During the charging process, Li + Migrate from the positive electrode and embed into the negative electrode, Li + The more the amount of embedded Li is, the greater the charging capacity of the battery is. During the discharge process, Li + Li is extracted from the negative electrode material and migrates back to the positive electrode. + The more the amount of intercalation and deintercalation, the greater the discharge capacity of the battery. Therefore, the performance of the negative electrode material is a key factor affecting the performance of lithium-ion batteries.
[0004] Hard carbon is one of the common negative electrode materials. It refers to carbon that is difficult to graphitize and is the pyrolytic carbon of high molecular polymers. It is widely used as the negative electrode material of lithium-ion batteries due to its high capacity, low cost and excellent cycle performance due to random arrangement. However, due to the disadvantages of too high electrode potential, potential hysteresis (i.e., the lithium insertion potential is lower than the lithium extraction potential), and large irreversible capacity in the first cycle, it has not yet been commercialized on a large scale. Researchers in this field have conducted a lot of modification studies to solve this problem. For example, patent CN107986254B discloses a method for preparing a hard carbon negative electrode material, which includes the following steps: kneading aggregate and asphalt with a softening point of 200-280°C at 300-380°C to obtain a mixture; molding the mixture, and carbonizing it at 400-500°C to obtain a precursor; crushing the precursor, and carbonizing it at 900-1400°C to obtain the hard carbon negative electrode material. Although its reversible specific capacity is improved, the interface bonding force between the aggregate and the asphalt is weak, resulting in poor cycle stability of the negative electrode material. Patent CN113113601B discloses a hard carbon negative electrode material for lithium ion secondary batteries and a preparation method thereof, wherein the hard carbon negative electrode material comprises: a hard carbon precursor, a phosphorus-containing dopant and a polymer, wherein the hard carbon precursor is prepared from a hard carbon raw material, the mass fraction of the phosphorus element in the phosphorus-containing dopant in the hard carbon negative electrode material is 0.3%-5%, at least a portion of the surface of the hard carbon negative electrode material is covered by the polymer, and the mass fraction of the polymer in the hard carbon negative electrode material is 1%-20%. It improves the first efficiency of hard carbon by doping with heteroatoms, but there is a problem of poor rate performance due to uneven doping.
[0005] Therefore, it is necessary to develop a hard carbon negative electrode material for lithium-ion batteries with excellent comprehensive performance and a preparation method thereof to meet the needs of high-performance development of lithium-ion batteries. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a preparation method of a surface-modified hard carbon negative electrode material for lithium-ion batteries. First, phenol, alkyl alcohol phenol compounds, and furfural are used as polycondensation raw materials, and hexamethylenetetramine is used as a curing agent to prepare furfural resin microspheres. Then, the furfural resin microspheres are modified with a thiophene silane coupling agent to obtain modified furfural resin microspheres with thiophene groups on the surface; then, the modified furfural resin microspheres are coated with polythiophene by a surface in-situ synthesis method, and carbonized to obtain a surface-modified hard carbon negative electrode material for lithium-ion batteries. The active sites formed by sulfur elements inside and on the surface of hard carbon can not only improve the adsorption capacity of lithium ions and improve the first coulomb efficiency, but also better bind lithium ions during the cycle process, reduce the disordered diffusion and loss of lithium ions, and improve the cycle stability. In addition, polythiophene is coated on the surface of the modified furfural resin microspheres by in-situ polymerization, which effectively improves the interface bonding force and the uniformity of sulfur doping, and avoids the weakening of rate performance and cycle stability.
[0007] In order to achieve the above purpose, the following technical solutions are adopted:
[0008] A method for preparing a surface-modified hard carbon negative electrode material for a lithium-ion battery comprises the following steps:
[0009] 1) Phenol, alkyl alcohol phenol compound and furfural are subjected to polycondensation reaction under the action of alkali solution, and furfural resin prepolymer is obtained after dehydration;
[0010] 2) dissolving the furfural resin prepolymer and hexamethylenetetramine in a solvent, adding a surfactant and mixing evenly to react, filtering, washing and drying after the reaction to obtain furfural resin microspheres;
[0011] 3) modifying the furfural resin microspheres with a thienylsilane coupling agent to obtain modified furfural resin microspheres;
[0012] 4) adding the modified furfural resin microspheres, alkylphenol polyoxyethylene ether, and thiophene monomer to an organic solvent to form a stable dispersion, adding an oxidant under an inert atmosphere, controlling the temperature to react, filtering after the reaction, washing with dilute hydrochloric acid, acetone, ethanol, and water in sequence, and drying to obtain a polythiophene-coated furfural resin precursor;
[0013] 5) The polythiophene-coated furfural resin precursor is carbonized to obtain a surface-modified lithium-ion battery hard carbon negative electrode material.
[0014] In step 1), the alkali solution is a sodium hydroxide solution with a concentration of 15-25wt%. The amount of sodium hydroxide used is 0.5-2wt% of the sum of the mass of phenol, alkyl alcohol phenol compound and furfural. The alkyl alcohol phenol compound is selected from one or a combination of two or more of p-hydroxybenzyl alcohol, 2-hydroxybenzyl alcohol, m-hydroxybenzyl alcohol, o-hydroxyphenylethanol, p-hydroxyphenylethanol and 3-hydroxyphenylethanol. The molar ratio of phenol, alkyl alcohol phenol compound and furfural is 0.7-0.9:0.1-0.3:1.1-1.3. The polycondensation reaction conditions are 60-90°C and constant temperature reaction for 3-6h. The dehydration conditions are vacuum degree 0.01-0.1MPa, temperature 60-80°C and time 0.5-1h.
[0015] The activity of the hydroxyl groups on alkyl alcohol phenol compounds is much lower than that of the active hydrogen on the hydroxymethyl group and the phenol ring. Using alkyl alcohol phenol compounds to replace part of phenol in the polycondensation reaction will result in residual hydroxyl groups on the obtained furfural resin microspheres, providing active hydroxyl groups for the preparation of modified furfural resin microspheres.
[0016] In step 2), the mass ratio of the furfural resin prepolymer, hexamethylenetetramine and surfactant is 100:10-15:2-4. The mass of the solvent is 3-4 times that of the furfural resin prepolymer. The solvent is selected from one or a combination of two or more of methanol, ethanol, ethylene glycol, isopropanol, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, toluene and pyridine. The surfactant is selected from one or a combination of two or more of polyvinyl alcohol, sodium dodecyl sulfate and sodium dodecyl sulfonate. The reaction conditions are 110-140°C for 2-5h. The washing is washing with water 1-3 times, and the drying is drying at 60-80°C to constant weight.
[0017] In step 3), the thienyl silane coupling agent is selected from one or a combination of triethoxy-2-thienyl silane and trimethoxy (thien-2-yl) silane, and the amount of the thienyl silane coupling agent is 3-5wt% of the furfural resin microspheres.
[0018] In step 3), the furfural resin microspheres are modified by a thienylsilane coupling agent as follows: the thienylsilane coupling agent is dissolved in an organic solvent to prepare a solution, the solution is added to the furfural resin microspheres for boiling reaction, filtering, and drying to obtain modified furfural resin microspheres. The reaction time is 12-24 hours. The organic solvent is selected from one or a combination of two or more of toluene, benzene, and chloroform. The solution concentration is 3-5wt%.
[0019] In step 4), the alkylphenol polyoxyethylene ether is selected from one or a combination of two or more of NP-10, NP-16, NP-20, OP-10, TX-7, TX-15, and TX-25, preferably NP-10. The organic solvent is selected from one or a combination of two or more of chloroform, n-hexane, dichloromethane, and acetonitrile. The oxidant is FeCl3. The mass ratio of the modified furfural resin microspheres, dispersant, thiophene monomer, and oxidant is 100:3-5:10-15:30-50. The mass of the organic solvent is 3-4 times that of the modified furfural resin microspheres. The thiophene monomer is selected from one or a combination of two or more of thiophene, 3-methylthiophene, and 3-ethylthiophene. The temperature control reaction is to control the temperature at 20-40°C for 12-24h. The concentration of the dilute hydrochloric acid in the reaction is 0.1-0.4mol / L. The drying is to dry at 60-80°C to constant weight.
[0020] In step 5), the carbonization treatment conditions are inert atmosphere, rising to 800-1500° C. at a rate of 3-5° C. / min, and keeping warm for 2-5 hours.
[0021] The present invention also provides a surface-modified lithium-ion battery hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention first uses phenol, alkyl alcohol phenol compounds, and furfural as polycondensation raw materials, and uses hexamethylenetetramine as a curing agent to prepare furfural resin microspheres, and then modifies the furfural resin microspheres with a thiophene silane coupling agent to obtain modified furfural resin microspheres with thiophene groups on the surface that can undergo polymerization reactions. Finally, the modified furfural resin microspheres are coated with polythiophene through a surface in-situ synthesis method, and carbonized to obtain a surface-modified lithium-ion battery hard carbon negative electrode material. The active sites formed by sulfur elements inside and on the surface of hard carbon can not only improve the adsorption capacity of lithium ions and enhance the initial coulomb efficiency, but also better bind lithium ions during the cycle, reduce the disordered diffusion and loss of lithium ions, and improve the cycle stability. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0025] Example 1
[0026] 1) 0.7 mol of phenol, 0.3 mol of m-hydroxybenzyl alcohol and 1.3 mol of furfural are subjected to polycondensation reaction at 90° C. for 5 h under the action of 15 wt % sodium hydroxide aqueous solution (the amount of sodium hydroxide used is 2 wt % of the total mass of phenol, alkyl alcohol phenol compound and furfural). After the reaction is completed, dehydration is performed at a vacuum degree of 0.095 MPa, a temperature of 80° C. and a time of 0.5 h to obtain a furfural resin prepolymer;
[0027] 2) dissolving 100 g of furfural resin prepolymer and 15 g of hexamethylenetetramine in 300 g of ethanol, adding 4 g of sodium dodecyl sulfate and mixing evenly to react, filtering after the reaction, washing with water for 3 times, and drying at 80° C. to constant weight to obtain furfural resin microspheres;
[0028] 3) dissolving 5 g of triethoxy-2-thienylsilane in 95 g of toluene to prepare a solution with a concentration of 5 wt %, adding 100 g of furfural resin microspheres, boiling and reacting for 12 h, filtering, and drying to obtain modified furfural resin microspheres with an average particle size of 15 μm;
[0029] 4) 100 g of modified furfural resin microspheres, 5 g of dispersant NP-10, and 15 g of thiophene were added to 300 g of chloroform to form a stable dispersion. Under a nitrogen atmosphere, 50 g of FeCl3 was added and the temperature was controlled at 20°C for reaction for 24 h. After the reaction was completed, the mixture was filtered and washed with 0.3 mol / L dilute hydrochloric acid, acetone, ethanol, and water in sequence. The mixture was dried at 80°C to constant weight to obtain a polythiophene-coated furfural resin precursor.
[0030] 5) In a nitrogen atmosphere, the polythiophene-coated furfural resin precursor was carbonized at a rate of 3°C / min to 1500°C for 3 h to obtain a surface-modified lithium-ion battery hard carbon negative electrode material.
[0031] Example 2
[0032] The rest is the same as Example 1, except that in step 1), the amount of m-hydroxybenzyl alcohol is 0.1 mol, and the amount of phenol is 0.9 mol.
[0033] Example 3
[0034] The rest is the same as Example 1, except that in step 4), the amount of thiophene used is 10 g.
[0035] Example 4
[0036] The rest is the same as Example 1, except that in step 3), 3 g of triethoxy-2-thienylsilane is used to prepare a 3 wt % solution.
[0037] Example 5
[0038] The rest is the same as Example 1, except that in step 3), the amount of furfural resin microspheres used is 80 g.
[0039] Example 6
[0040] The rest is the same as Example 1, except that in step 3), the amount of furfural resin microspheres used is 200 g.
[0041] Example 7
[0042] 1) 0.9 mol of phenol, 0.3 mol of m-hydroxybenzyl alcohol and 1.1 mol of furfural are subjected to polycondensation reaction at 90° C. for 5 h under the action of 15 wt % sodium hydroxide aqueous solution (the amount of sodium hydroxide used is 2 wt % of the total mass of phenol, alkyl alcohol phenol compound and furfural). After the reaction is completed, dehydration is performed at a vacuum degree of 0.095 MPa, a temperature of 80° C. and a time of 0.5 h to obtain a furfural resin prepolymer;
[0043] 2) dissolving 100 g of furfural resin prepolymer and 10 g of hexamethylenetetramine in 300 g of ethanol, adding 4 g of sodium dodecyl sulfate and mixing evenly to react, filtering after the reaction, washing with water for 3 times, and drying at 80° C. to constant weight to obtain furfural resin microspheres;
[0044] 3) dissolving 5 g of triethoxy-2-thienylsilane in 95 g of toluene to prepare a solution with a concentration of 5 wt%, adding 100 g of furfural resin microspheres, boiling and reacting for 12 h, filtering, and drying to obtain modified furfural resin microspheres;
[0045] 4) 100 g of modified furfural resin microspheres, 3 g of dispersant NP-20, and 15 g of thiophene were added to 300 g of chloroform to form a stable dispersion. Under a nitrogen atmosphere, 30 g of FeCl3 was added, and the temperature was controlled at 20°C for reaction for 24 h. After the reaction was completed, the mixture was filtered, washed with 0.3 mol / L dilute hydrochloric acid, acetone, ethanol, and water in sequence, and dried at 80°C to constant weight to obtain a polythiophene-coated furfural resin precursor;
[0046] 5) In a nitrogen atmosphere, the polythiophene-coated furfural resin precursor was carbonized at a rate of 3°C / min to 1500°C for 3 h to obtain a surface-modified lithium-ion battery hard carbon negative electrode material.
[0047] Comparative Example 1
[0048] The rest is the same as Example 1, except that step 3) is: 5 g of 2-thiopheneacetyl chloride is dissolved in 180 g of toluene, 100 g of furfural resin microspheres are added and ultrasonically dispersed uniformly, 3.5 g of triethylamine is added, and the temperature is controlled at 35° C. to react for 5 h. After the reaction is completed, it is filtered, washed alternately with ethanol and water for 3 times, and dried at 60° C. to constant weight to obtain modified furfural resin microspheres.
[0049] Comparative Example 2
[0050] The rest is the same as Example 1, except that in step 1), phenol is used in an equal molar amount to replace m-hydroxybenzyl alcohol.
[0051] Comparative Example 3
[0052] The rest is the same as Example 1, except that step 4) is omitted, that is, the modified furfural resin microspheres are not coated with polythiophene, and the carbonization treatment of step 5) is directly performed.
[0053] Comparative Example 4
[0054] The rest is the same as Example 1, except that step 3) is omitted, and the furfural resin microspheres obtained in step 2) are directly subjected to step 4).
[0055] Application Examples
[0056] Preparation of electrode: The surface modified lithium ion battery hard carbon negative electrode material, acetylene black and PVDF were mixed in a mass ratio of 8:1:1, N-methyl-2-pyrrolidone was used as solvent, and the mixture was evenly stirred and coated on a 10 μm thick copper foil. The mixture was dried in a vacuum drying oven at 120°C with a vacuum degree of 0.085 MPa for 12 h, and rolled into a 14 mm electrode sheet for later use.
[0057] Battery assembly: A CR2016 button cell case was used, the counter electrode was a 16 mm lithium metal sheet, a room temperature EC+DEC mixed system containing 1 mol / L LiPF6 (volume ratio of 1:1) was used as the electrolyte, and the diaphragm was a PP film with a thickness of 16 μm and a diameter of 16 mm. The assembly was carried out in an argon glove box.
[0058] The battery prepared in the above application example was tested for the following performances:
[0059] The battery was tested for constant current charge and discharge cycles at a current density of 1C in the voltage range of 0-3V using the Blue Electric charge and discharge system. The first reversible capacity and first efficiency were tested at 0.2C.
[0060] Table 1 Performance test results
[0061]
[0062] It can be seen from Table 1 that the surface modified lithium ion battery hard carbon negative electrode material prepared by the present invention can give the lithium ion battery excellent rate performance, first coulombic efficiency and cycle stability.
[0063] From Example 1, Examples 4-6, and Comparative Example 1, it can be seen that the use of triethoxy-2-thienylsilane is beneficial to the improvement of the first efficiency and cycle stability. It is speculated that: on the one hand, the silicon element can adjust the hard carbon structure, making it more conducive to the insertion and extraction of lithium ions during the first charge and discharge process, reducing the resistance of lithium ions during the insertion process, and improving the first coulomb efficiency; on the other hand, it strengthens the skeleton structure of hard carbon, maintains its integrity, and improves cycle stability. That is, the co-doping of sulfur and silicon produces a synergistic effect on the improvement of the electrochemical performance of hard carbon.
[0064] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a surface-modified hard carbon negative electrode material for a lithium-ion battery, characterized in that: The steps include: 1) Phenol, alkyl alcohol phenol compound and furfural are subjected to polycondensation reaction under the action of alkali solution, and furfural resin prepolymer is obtained after dehydration; 2) dissolving the furfural resin prepolymer and hexamethylenetetramine in a solvent, adding a surfactant and mixing evenly to react, filtering, washing and drying after the reaction to obtain furfural resin microspheres; 3) modifying the furfural resin microspheres with a thienylsilane coupling agent to obtain modified furfural resin microspheres; 4) adding the modified furfural resin microspheres, alkylphenol polyoxyethylene ether, and thiophene monomer to an organic solvent to form a stable dispersion, adding an oxidant under an inert atmosphere, controlling the temperature to react, filtering after the reaction, washing with dilute hydrochloric acid, acetone, ethanol, and water in sequence, and drying to obtain a polythiophene-coated furfural resin precursor; 5) The polythiophene-coated furfural resin precursor is carbonized to obtain a surface-modified lithium-ion battery hard carbon negative electrode material.
2. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 1), the molar ratio of phenol, alkyl alcohol phenol compound and furfural is 0.7-0.9:0.1-0.3:1.1-1.
3.
3. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 1), the alkyl alcohol phenol compound is selected from one or a combination of two or more of p-hydroxybenzyl alcohol, 2-hydroxybenzyl alcohol, m-hydroxybenzyl alcohol, o-hydroxyphenylethanol, p-hydroxyphenylethanol, and 3-hydroxyphenylethanol.
4. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 2), the mass ratio of the furfural resin prepolymer, hexamethylenetetramine and surfactant is 100:10-15:2-4. The mass of the solvent is 3-4 times that of the furfural resin prepolymer.
5. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 3), the thienyl silane coupling agent is selected from one or a combination of triethoxy-2-thienyl silane and trimethoxy (thien-2-yl) silane, and the amount of the thienyl silane coupling agent is 3-5wt% of the furfural resin microspheres.
6. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 3), the furfural resin microspheres are modified by a thienyl silane coupling agent by dissolving the thienyl silane coupling agent in an organic solvent to prepare a solution, adding the furfural resin microspheres to a boiling reaction, filtering, and drying to obtain modified furfural resin microspheres.
7. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 4), the alkylphenol polyoxyethylene ether is selected from one or a combination of two or more of NP-10, NP-16, NP-20, OP-10, TX-7, TX-15, and TX-25, preferably NP-10; the organic solvent is selected from one or a combination of two or more of chloroform, n-hexane, dichloromethane, and acetonitrile; and the oxidant is FeCl3.
8. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 4), the mass ratio of the modified furfural resin microspheres, the dispersant, the thiophene monomer, and the oxidant is 100:3-5:10-15:30-50.
9. The method for preparing the surface-modified hard carbon negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In step 4), the thiophene monomer is selected from one or a combination of two or more of thiophene, 3-methylthiophene, and 3-ethylthiophene.
10. A surface-modified lithium-ion battery hard carbon negative electrode material, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A method for preparing hard carbon anode material
CN107986254B
A hard carbon anode material for lithium-ion secondary batteries and its preparation method
CN113113601B